2007
DOI: 10.1073/pnas.0609396104
|View full text |Cite
|
Sign up to set email alerts
|

Charged polycyclic aromatic hydrocarbon clusters and the galactic extended red emission

Abstract: The species responsible for the broad extended red emission (ERE), discovered in 1975 and now known to be widespread throughout the Galaxy, still is unidentified. Spanning the range from Ϸ540 to 900 nm, the ERE is a photoluminescent process associated with a wide variety of different interstellar environments. Over the years, a number of plausible candidates have been suggested, but subsequent observations ruled them out. The objects that present the ERE also emit the infrared features attributed to free polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 49 publications
0
116
0
Order By: Relevance
“…Finally, laboratory spectroscopic studies on [PAH 2 ] + are needed to progress in this identification. In particular, closed-shell cation dimers as proposed by Rhee et al (2007) deserve additional studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, laboratory spectroscopic studies on [PAH 2 ] + are needed to progress in this identification. In particular, closed-shell cation dimers as proposed by Rhee et al (2007) deserve additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent theoretical work (Rhee et al 2007), it was shown that charged PAH dimers ([PAH 2 ] + ), more specifically the subclass made of closed-shell species, can fluoresce in the ERE range with a quantum yield that is consistent with this emission. The overlays of Figs.…”
Section: The Case Of [Pah 2 ] +mentioning
confidence: 99%
“…Recently, two fullerene molecules (C60 and C70) have been identified in a carbon rich planetary nebulae (Cami et al 2010). It is proposed that the identification of individual PAH molecules could help to resolve some of the mysteries associated with the diffuse interstellar bands (DIBs; Salama et al 1999;Snow 2001) and the galactic extended red emission (ERE; Rhee et al 2007). Similar to PAHs, spectroscopic signatures of nitrogen containing polycyclic aromatic hydrocarbons (PANH) are prevalent in various cosmological environments (Hudgins et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the cationic complexes are bound by both electrostatic and covalent interactions. Closed and open shell PAH dimers are estimated to be bound by energies of about 20 kcal mol −1 , and absorb in the visible and sometimes in the infrared (Rhee et al 2007;Weisman et al 2005). The cationic complexes of small olefins, especially the nitrogen containing ones, have not been explored in any detail.…”
Section: Introductionmentioning
confidence: 99%
“…The carriers of the ERE are widespread throughout the diffuse interstellar medium of the Milky Way Galaxy and other galaxies (Rhee et al 2007, Berné et al 2008, Witt et al 2008.…”
Section: Overviewmentioning
confidence: 99%